Photocatalytic performances and activities of Ag-doped CuFe 2O4 nanoparticles - Zhu, Z.; Li, Xin Yong; Zhao, Q.; Li, Y.; Sun, C.; Cao, Y. (2013)
In this work, CuFe2O4 nanoparticles were synthesized by a chemical co-precipitation route. The Ag/CuFe2O4 catalyst was prepared based on the CuFe2O4 nanoparticles by the incipient wetness impregnation strategy, which showed excellent photoelectric property and catalytic activity. The structural properties of these samples were systematically investigated by X-ray powder diffraction (XRD), transmission electronic microscopy (TEM), UV-vis diffuse reflectance spectroscopy (DRS), X-ray photoelectron spectroscopy (XPS) and Fourier transform infrared spectroscopy (FT-IR) techniques. The photo-induced charge separation in the samples was demonstrated by surface photovoltage (SPV) measurement. The photocatalytic degradation of 4-CP by the Ag/CuFe2O4 and CuFe2O4 samples were comparatively studied under xenon lamp irradiation. The results indicate that the Ag/CuFe2O4 sample exhibited the higher efficiency for the degradation of 4-CP.